Development of Tretinoin-Loaded Nanostructured Lipid Carrier and Hyaluronic Acid Topical Gel - Subramanian, S. (Asian Journal of Pharmaceutics (AJP), 2023)
The current study was focussed on the fabrication of nanostructered lipid carrier (NLC) of tretinoin (TRE) followed by its incorporation into hyaluronic acid (HA)-loaded carbapol 940 gel aiming to improve acne treatment. Materials and Methods: The TRE-NLC was fabricated using melt-emulsification and ultrasonication method. The fabricated NLC was studied for its particle size, zeta potential, polydispersity index, morphology, and entrapment efficiency of TRE. The gel containing HA and TRE-NLC were evaluated for pH, spreadability, extrudability, bloom strength, and viscosity. The in vitro release studies and in vitro occlusivity test for the formulated gel and marketed gel were carried out. Results and Discussion: The formulated gel showed better release of 86.32% when compared to marketed gel with 38.52% release in 8 h. Occlusion factor can be related to skin hydration based upon the ability to prevent water loss from the surface of the skin which was found to be 42.29% for the formulated gel and 4.76% for the marketed gel. Conclusion: The combination of TRE-loaded NLCs and HA gel may provide a more effective treatment for acne by diminishing the dryness than either TRE or HA gel alone.